2008
DOI: 10.1037/0096-1523.34.1.137
|View full text |Cite
|
Sign up to set email alerts
|

The task rule congruency effect in task switching reflects activated long-term memory.

Abstract: Reaction time task rule congruency effects (RT-TRCEs) reflect faster responses to stimuli for which the competing task rules indicate the same correct response than to stimuli indicating conflicting responses. The authors tested the hypothesis that RT-TRCE reflects activated overlearned response category codes in long-term memory (such as up or left). The results support the hypothesis by showing that (a) RT-TRCE was absent for tasks for which there were no response codes ready beforehand, (b) RT-TRCE was pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
156
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 119 publications
(161 citation statements)
references
References 95 publications
(198 reference statements)
3
156
2
Order By: Relevance
“…RTs and accuracies were each subjected to a 3 =4.52, r²=.54, no such effect was present in the Verbal Diagnostic Task condition, t(16)= 1.12, p>.13, r²=.08. In other words, the error rates were thus only partly in line the RT-data, which might suggest that with respect to the task-rule congruency effect, RT and error-rates are elicited by different processes (e.g., Meiran & Kessler, 2008). Yet, in view of the absence of an effect in this one contrast, it would be premature to draw conclusions at this stage…”
mentioning
confidence: 86%
See 4 more Smart Citations
“…RTs and accuracies were each subjected to a 3 =4.52, r²=.54, no such effect was present in the Verbal Diagnostic Task condition, t(16)= 1.12, p>.13, r²=.08. In other words, the error rates were thus only partly in line the RT-data, which might suggest that with respect to the task-rule congruency effect, RT and error-rates are elicited by different processes (e.g., Meiran & Kessler, 2008). Yet, in view of the absence of an effect in this one contrast, it would be premature to draw conclusions at this stage…”
mentioning
confidence: 86%
“…We were especially interested if such task-sets could trigger responses when being irrelevant in the context of another task. Because previous research (Cohen-Kdoshay & Meiran, 2007;2009;De Houwer et al, 2005;Meiran & Kessler, 2008;Waszak et al, 2008;Wenke et al, 2007;2009) indicate that responses in instruction-based task-sets are represented in terms of conceptual codes (e.g., -left‖ or -right‖) without further specification. Experiment 2 showed that tasksets eliciting such effects are formed only when participants intend to enact the instructed task.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations